2008
DOI: 10.1021/ol8011138
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Hydrophosphorylation and Hydrophosphinylation of Cyclopropenes

Abstract: Novel transition-metal-catalyzed addition of P-H entities across the cyclopropene double bond has been developed. This transformation allows for mild and efficient preparation of phosphorus-containing cyclopropanes in good yields and high degrees of diastereoselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 43 publications
(18 reference statements)
0
23
0
Order By: Relevance
“…For example, Pagenkopf and coworkers reported Rh-catalyzed selective addition of mixed terminal alkenes and alkynes [29]. Rubin and coworkers also used 19 in their Pd-catalyzed HeP(O) addition to cyclopropenes [30]. Carpentier and coworkers also used 19 in selective addition to dienes [31].…”
Section: Addition Of H-phosphonates (Ro) 2 P(o)h To Alkynesmentioning
confidence: 99%
“…For example, Pagenkopf and coworkers reported Rh-catalyzed selective addition of mixed terminal alkenes and alkynes [29]. Rubin and coworkers also used 19 in their Pd-catalyzed HeP(O) addition to cyclopropenes [30]. Carpentier and coworkers also used 19 in selective addition to dienes [31].…”
Section: Addition Of H-phosphonates (Ro) 2 P(o)h To Alkynesmentioning
confidence: 99%
“…Being an efficient electron-withdrawing group, the carboxamide function stabilizes the reactive strained double bond; however, unlike esters, amides are much less sensitive to strong bases and are compatible with the conditions used for generation of cyclopropenyl anion ( 4 ) (path a , Scheme 1). 1 Carboxamide substituents can be used to control facial selectivity in addition reactions to cyclopropenes, as was demonstrated in the sterically-controlled palladium-catalyzed addition of H-P entities (path b ) 2 and carboxamide-directed, base-assisted nucleophilic additions of alkoxides and azoles (path c ). 3 The amide functionality could also serve as an efficient electron-pulling entity to trigger “push-pull” ring-opening in the nucleophilic addition of amines to cyclopropenes (path d , Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The author suggested that the diastereoselectivity of hydrophosphorylation was mainly controlled by sterics (Scheme 26). 90 Previously, hydroformylation of cyclopropenes was represented by a few stoichiometric reactions mediated by stoichiometric amounts of HMn(CO) 5 or HCo(CO) 4 , reported by Orchin [91][92][93] and Noyori. 94 View Online of prochiral cyclopropenes to produce tri-and tetrasubstituted cyclopropylcarboxaldehydes, proceeding under mild conditions and very low catalyst loading (TON = 750-1500).…”
Section: Hydrometalation Reactionsmentioning
confidence: 99%